A comparative study of transformations on noun and verb phrases in normals and aphasics - Pavri, Meher (Journal of All India Institute of Speech and Hearing)
Noam Chomsky (1965) put forward the hypothesis that the transformations applied to the verb phrase easier to compIehend than thqse applied to the noun phrase and thus a greater number of transformations on the verb phrase could be comprehended than on the noun phrase. Goodglass and Myerson (1969), however, found the opposite results (that is, noun phrase transformations we’re easier to comprehend than the ones applied to the verb phrase) while experimenting on aphasic subjects.